Suboptimal infection prevention and control in the healthcare culture - Cioffi, Domenico; Cioffi, Jane (International Journal of Infection Control, 2019)
Healthcare associated infections are one of the most common complications of hospitalised patients although they are largely preventable through compliance with infection prevention and control standards and guidelines. Clinical performance has been associated with culture in health care. By exploring the influence of culture in health care on infection prevention and control practice, understanding and insight into suboptimal IPC practice may be exposed. This paper discusses the cultural milieu of IPC practice and embedded norms proposing a cultural shift is mandatory to address suboptimal IPC practice. Recommendations are made that a cultural shift to blend the cure and prevention paradigms that effectively supports optimal infection prevention and control practice be envisaged by healthcare workers and implemented.